2021
DOI: 10.2507/ijsimm20-2-558
|View full text |Cite
|
Sign up to set email alerts
|

Meso-Scale Simulations of Lightweight Aggregate Concrete under Impact Loading

Abstract: To reveal the damage evolution and energy dissipation characteristics of lightweight aggregate concrete (LWAC) under impact loading, some simulations of lightweight shale ceramsite concrete under high strain rate impact with a 3D meso-scale model were carried out. After the meso-scale model considering the randomness of the shape and distribution of lightweight aggregates being established and the material parameters of each component being determined by test results, the damage evolution and energy dissipatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…According to the method illustrated in the literature (Xie et al, 2019), the basic physical parameters of RO, G, F C , T, P crush , and μ crush are obtained from the laboratory test, and crushed stones and gravel parameters are provided by the manufacturer. The parameters of the state and damage equations can be found in the literature (Wang et al, 2021;Lv et al, 2018). The rest of the parameters are determined through the simulation test.…”
Section: Holmquist-johnson-cook Constitutive Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the method illustrated in the literature (Xie et al, 2019), the basic physical parameters of RO, G, F C , T, P crush , and μ crush are obtained from the laboratory test, and crushed stones and gravel parameters are provided by the manufacturer. The parameters of the state and damage equations can be found in the literature (Wang et al, 2021;Lv et al, 2018). The rest of the parameters are determined through the simulation test.…”
Section: Holmquist-johnson-cook Constitutive Modelmentioning
confidence: 99%
“…Yu et al (2021) changed the parameters of the HJC constitutive model and studied the influence of the strength of aggregate and mortar on the overall performance. Wang et al (2021) established a 3D mesoscopic model to study the damage and energy dissipation process of concrete. Ai et al (2013) simulated the mesoscopic failure mechanism of the concrete materials based on LS-DYNA software.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 presents the quasi-static mechanical parameters of the three-phase random aggregate model at 20°C, based on previous literature (Wang et al 2021a;Wu et al 2020a;Jin et al 2020;Liu 1999;Chen 2007). In this table, the data marked with "a" were obtained from Wang et al (2021a); data marked with "b" were collected from Jin et al (2020); data marked with "c" were calculated in the same way as Chen (2017); data marked with "d" were determined using the calculation method proposed by Liu (1999) and the data marked with "e" were calculated using the equation proposed by Goto et al (1979). The other parameters are determined via a trial calculations method.…”
Section: Selection Of Mechanical Parameters Of Materialsmentioning
confidence: 99%
“…The original stress wave applied at the end of the incident rod was derived from a previous study (Wang et al 2021a), as shown in Fig. 9.…”
Section: Establishment Of the Finite Element Modelmentioning
confidence: 99%
See 1 more Smart Citation